Psychological aspects of breast cancer for women during the menopause - Guglas, Natalia; Mackiewicz, Jacek; Pawlik, Piotr; Cichy, Wojciech (Menopause Review/Przegląd Menopauzalny, 2007)
Breast cancer is the main cause of death of women in Poland. The morbidity rate for this cancer is invariably on the increase. Of considerable significance is certainly the age at which one is stricken with the cancer. The most ill-timed period for breast cancer to appear is the menopause, the period when, apart from any standard cancer-related ailments, women undergo violent menopause-related changes as far as both their psyches and their bodies are concerned. The social, economic and familial circumstances of the diseased undergo similar changes. Cancers are usually accompanied by intensely negative emotional reactions such as fear and immense uneasiness. These emotions overlap with those characteristic for the menopause, such as the lack of emotional stability, vascular and locomotory disorders, the impression of being physically unattractive – all of which can result in depression. It is of vital importance that cancer-stricken women are taken care of in both a strictly medical and psychological sense; extra-medical emotional assistance can also prove crucial here. The goal of the present paper is to underline the fact that identification of nipple gland cancer during the menopause is an additional major burden, both physical and emotional. An important part of the therapy is to provide the diseased and their families with an all-around medical and psychological care. This is especially important during the menopause, when the hitherto-stable female roles of a mother and a wife are severely upset. All of the above relies heavily on the active co-operation of each and every member of the medical staff and on the individual approach to each and every patient